Idursulfase pharmacokinetics, cellular uptake, and pharmacodynamics: Effect of sialylation and manufacturing process. Issue 12 (14th October 2020) - Garcia, Antony R.; Lamsa, Justin; Whiteman, David A. H.; Muenzer, Joseph
Abstract: Recombinant iduronate‐2‐sulfatase (idursulfase) is available for the treatment of mucopolysaccharidosis II (MPS II). The effectiveness of this glycoprotein may depend on post‐translational modifications such as glycosylation and sialylation during manufacture. We assessed the effects of sialylation level and the scale‐up of idursulfase production on the pharmacokinetics, cellular uptake and pharmacodynamics of idursulfase in Sprague Dawley rats and mice (knock‐out model of MPS II and wild type). Serum clearance in rats decreased with an increase in idursulfase sialylation, from 2.23 mL/min/kg with 7.4 mol sialic acid (SA)/mol idursulfase to 0.57 mL/min/kg with 16.9 mol SA/mol idursulfase. In mice, 31%‐52% of the infused idursulfase dose was detected in the liver. The idursulfase uptake into the liver was not affected by sialylation, but high sialylation led to lower uptake in the spleen and greater uptake in the kidney and heart in both wild‐type and MPS II mice. The pharmacodynamics study revealed a greater reduction of glycosaminoglycan levels with high idursulfase sialylation in the kidney, which reflects the higher idursulfase uptake into this organ with higher sialylation. There was no effect of manufacturing process on any idursulfase characteristic, suggesting that production scale‐up would have no impact on clinical effectiveness. Abstract : The effectiveness of idursulfase in treating the rare lysosomal storage disease mucopolysaccharidosis II may depend on post‐translational modifications such as glycosylation and sialylation during manufacture. Our findings in rodent models have shown that the rate of idursulfase uptake into tissue depends on the target organ as well as the degree of sialylation. In particular, the uptake of idursulfase in the liver was much greater than in any other tissue analyzed.